Decoration of RGD-mimetic porous scaffolds with engineered and devitalized extracellular matrix for adipose tissue regeneration. (June 2018) - Rossi, Eleonora; Guerrero, Julien; Aprile, Paola; Tocchio, Alessandro; Kappos, Elisabeth A.; Gerges, Irini; Lenardi, Cristina; Martin, Ivan; Scherberich, Arnaud
Graphical abstract: Abstract: Fat grafting is emerging as a promising alternative to silicon implants in breast reconstruction surgery. Unfortunately, this approach does not provide a proper mechanical support and is affected by drawbacks such as tissue resorption and donor site morbidity. Synthetic scaffolds can offer a valuable alternative to address these challenges, but poorly recapitulate the biochemical stimuli needed for tissue regeneration. Here, we aim at combining the positive features of a structural, synthetic polymer to an engineered, devitalized extracellular matrix (ECM) to generate a hybrid construct that can provide a mix of structural and biological stimuli needed for adipose tissue regeneration. A RGD-mimetic synthetic scaffold OPAAF, designed for soft tissue engineering, was decorated with ECM deposited by human adipose stromal cells (hASCs). The adipoinductive potential of the hybrid ECM-OPAAF construct was validated in vitro, by culture with hASC in a perfusion bioreactor system, and in vivo, by subcutaneous implantation in nude mouse. Our findings demonstrate that the hybrid ECM-OPAAF provides proper mechanical support and adipoinductive stimuli, with potential applicability as off-the-shelf material for adipose tissue reconstruction. Statement of Significance: In this study we combined the functionalities of a synthetic polymer with those of an engineered and subsequently devitalized extracellular matrix (ECM) to generate a hybrid material for adipose tissue regeneration. The developed hybrid ECM-OPAAF was demonstrated to regulate human adipose stromal cells adipogenic commitment in vitro and adipose tissue infiltration in vivo . Our findings demonstrate that the hybrid ECM-OPAAF provide proper mechanical support and adipoinductive stimuli and represents a promising off-the-shelf material for adipose tissue reconstruction. We believe that our approach could offer an alternative strategy for adipose tissue reconstruction in case of mastectomy or congenital abnormalities, overcoming the current limitations of autologous fat based strategies such as volume resorption and donor site morbidity.